The potential application of artificial intelligence in veterinary clinical practice and biomedical research - Akinsulie, Olalekan Chris; Idris, Ibrahim; Aliyu, Victor Ayodele; Shahzad, Sammuel; Banwo, Olamilekan Gabriel; Ogunleye, Seto Charles; Olorunshola, Mercy; Okedoyin, Deborah O.; Ugwu, Charles; Oladapo, Ifeoluwa Peace; Gbadegoye, Joy Olaoluwa; Akande, Qudus Afolabi; et al. (Frontiers in Veterinary Science, 2024)
Artificial intelligence (AI) is a fast-paced technological advancement in terms of its application to various fields of science and technology. In particular, AI has the potential to play various roles in veterinary clinical practice, enhancing the way veterinary care is delivered, improving outcomes for animals and ultimately humans. Also, in recent years, the emergence of AI has led to a new direction in biomedical research, especially in translational research with great potential, promising to revolutionize science. AI is applicable in antimicrobial resistance (AMR) research, cancer research, drug design and vaccine development, epidemiology, disease surveillance and genomics. Here, we highlighted and discussed the potential impact of various aspects of AI in veterinary clinical practice and biomedical research, proposing this technology as a key tool for addressing pressing global health challenges across various domains.